(untitled) (Interdisciplinary Studies Journal, 2025)
This study investigates the relationship between mental health and the use of anabolic steroids by emerging adults who practice bodybuilding. The literature review points out that cultural pressures and ideals of the male body, promoted by the media, influence the use of these substances. In addition to the physical impacts, the use of steroids also impacts the mental health of users, leading to problems ranging from mood disorders, self-image disorders and increased aggressiveness. The results confirm the hypothesis that the use of anabolic androgenic steroids is motivated by psychosocial factors, as well as negatively affecting the mental health of users.